The Management of Interpersonal Communication in A Long Distance Relationship Amongst college Students in The Context of Romantical Relationship (Studies on Diponegoro University Students who Undergo Long Distance Relationship with Their Partner). - Z, Zamratul Khairani; Lestari, Sri Budi; Purbaningrum, Dwi; Naryoso, Agus (Interaksi Online, 2016)
Long-distance romance relation carried by college students occur due to factors ofeducation or the demands of the profession that requires one of those pairs toproceed to move to other cities. The communication process they undergoheavily relying on the communication media they use. But the medium ofcommunication can also be a major cause of the resistance in a long distance romanceeither due to misunderstanding or network disruption in interpersonal communicationis ineffective against his partner can be a threat or an obstacle for couples whoundergo long distance romance.This study aims to find out how interpersonal communication is done by couplesand the decision-making process in resolving conflicts that arise in the relationshipsof romance/appear remote. The method used in this studyis descriptive qualitative data analysis and interpretation by using the method ofconstant comparison which generally includes process. This study usesa Tringular Theory of Love and Self Disclosure as the Foundation of research,and Attribution Theory on conflict management is used to describe the experience ofthe subjects. The data collection technique is conducted in-depth interviews with thestudents of the Diponegoro University who are living a long distancerelationship and their partner located outside the city of Semarang, Central Java.Communications management which is done by the students who undergo longdistance romance with their partner is to utilize the existing free time as good aspossible to establish communication. Each pair instill the importanceof communication and maximize the self disclosure. The existence of theflurry of respectively, making each pair also instilling mutual trust, in addition to astrong commitment which is owned will not lead to break up although conflict mayconduct often. In conflict management, avoidance behavior occurs at the beginningof the conflict, along with cooperative attitude which also carried the couple whenovercoming the problems.